E-Health for All - Is India Ready? - Soumya Patnaik; Amar Narayan Patnaik (Medsci Publications, 2015)
Over the last couple of decades, developments in the information and communication technology have made the most palpable impact on health care management all over the world. Newer terms like tele- medicine, e-health, telehealth and digital health surfaced to encom- pass broad concepts like electronic medical records and hospital au- tomation, telemedicine, e-learning in health sector, e-governance and so forth. Tele-medicine refers to the application of various tele- communication and networking systems in the delivery of appropri- ate health care to individuals without limitations of time or distance. It involves the speedy transmission of patient data related to consul- tations, diagnostic and therapeutic services, patient education and rehabilitative services among the providers, the consumers, the plan- ners and researchers. The advantages range from reduction of travel time and expenses for the patient, optimization of resources, en- hanced diagnostic and therapeutic quality, emergency management and early referral of critical cases, cost-effective delivery of specia- lized services (like follow-up after surgeries) and continued patient education and medical training. These novel concepts showed prom- ising results in several pilot projects in India and now the time has come to apply them to the all corners of the country. In this review we tried to search all relevant published data on the introduction of e-health concepts, programs, and the initial results so far from such efforts both from the governmental and non- governmental agencies and analyze the barriers and their possible solutions and to finally answer if India is ready to deliver e-health for all.